Pengaruh Pembelajaran Berbasis Masalah Terhadap Kemampuan Penalaran dan Komunikasi Matematis Siswa SMP - Rasmuin Rasmuin; Khusnul Khatima (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The objective in this research was to know there is or not an effect of problem based learning toword the ability in logical reasoning and mathematical communication of the student in SMP Negeri 9 Buton Tengah, Mawasangka Timur Subdistrict, Buton Tengah Regency. This research was quantitative research and using quasi experimental. Population in this research was grade VIII SMP Negeri 9 Buton Tengah conof 72 student. Sampel in this research was grade VIII1 with 36 student and grade VIII2 consisted of 36 students. The Technicque used in taking the sample was random sampling. While the instrument used was test. Data analysis techniques used in this research ware descriptive and inferential analysis. Based on the calculation by using independent samples t-test obtained the score that tcount as 1.013. for the score of the ttabel at the level of significance 0,05 (5%) and db = 70 that was 2.000. based on the score tcount >ttabel , then the hypotesis of the research was accepted. So that, it could be concluded that problem based learning had a significant effect toward the ability in logical reasoning and matematical communication of the student at grade VIII SMP Negeri 9 Buton Tengah.